2018
DOI: 10.1108/ijlls-06-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

A literature review of lesson study in initial teacher education

Abstract: Abstract• Purpose -A structured review of literature on Lesson Study (LS) in initial teacher education (ITE) was conducted. The focus was on how learning and observation were discussed in studies of LS in ITE.• Design -Each national team (in Norway and England) undertook independent searches of published peer-reviewed articles. The resulting articles were then combined, screened and collaboratively reviewed, the focus being on two areas of enquiry: 1) How learning is represented and discussed;2) The extent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 34 publications
5
57
0
3
Order By: Relevance
“…As researchers around the globe have increasingly started to examine LS in different educational contexts and settings aiming to determine its successful mechanisms and effects on teacher and student learning (Dudley et al, 2019), the knowledge base around LS is growing rapidly. However, although the impact of participating in LS on teachers' knowledge, skills and attitudes (Vermunt et al, 2019), the school context (Schipper et al, 2020), and student learning becomes more evident (Lewis and Perry, 2017), LS in initial teacher education (ITE) has received relatively little attention in research, despite a recent peak of publications (Cajkler and Wood, 2020;Larssen et al, 2018). Moreover, LS in Dutch ITE has not been thoroughly examined yet, and we argue that this article is one of the first studies that explores this context.…”
Section: Dutch Initial Teacher Educationmentioning
confidence: 99%
“…As researchers around the globe have increasingly started to examine LS in different educational contexts and settings aiming to determine its successful mechanisms and effects on teacher and student learning (Dudley et al, 2019), the knowledge base around LS is growing rapidly. However, although the impact of participating in LS on teachers' knowledge, skills and attitudes (Vermunt et al, 2019), the school context (Schipper et al, 2020), and student learning becomes more evident (Lewis and Perry, 2017), LS in initial teacher education (ITE) has received relatively little attention in research, despite a recent peak of publications (Cajkler and Wood, 2020;Larssen et al, 2018). Moreover, LS in Dutch ITE has not been thoroughly examined yet, and we argue that this article is one of the first studies that explores this context.…”
Section: Dutch Initial Teacher Educationmentioning
confidence: 99%
“…Nevertheless, the authors do not propose lesson study as the "the ultimate solution" to problems of initial teacher education in Turkey because prior research also showed certain shortcomings of lesson study practice specifically in initial teacher education. In an extensive review by Larssen et al, (2018), the authors underlined two critical bottom-lines to consider in order to strengthen lesson study practice and research. First, the concept of "learning" should be very clear for all lesson study stakeholders.…”
Section: Initial Language Teacher Education Can Be Revisited With Lesmentioning
confidence: 99%
“…Por otro lado, es importante retomar la importancia de la práctica educativa a partir de la planificación. De acuerdo con Larssen et al (2018), quienes realizaron en el mismo sentido una investigación documental, afirman que es sumamente fundamental construir una planeación de calidad y para ello, los investigadores enfatizan la importancia de la planeación colaborativa, en el contexto del estado mexicano, este se puede extrapolar al ámbito de los planes de trabajo que se desarrollan en un nivel de colegiado, consejo técnico o bien, en reuniones de academia. Asimismo, se tiene como ejemplar la indagación realizada por Tagle et al (2020) quienes tuvieron como propósito identificar los tipos de conocimiento que se activaban por parte de los maestros en su proceso de formación docente al diseñar la planeación didáctica.…”
Section: Conclusionesunclassified